Retrobulbar hematoma: A systematic review of factors related to outcomes. Issue 2 (February 2018) - Christie, Brian; Block, Lisa; Ma, Yue; Wick, Alexandra; Afifi, Ahmed
Summary: Introduction: Retrobulbar hematoma (RBH), a rare but serious condition, can result in permanent vision loss. Although it is a known complication following trauma or facial fracture reduction, sinus surgery, or blepharoplasty, factors related to patient outcomes are not well-defined. A systematic review was performed to determine the relation of patient/treatment factors to outcomes. Methods: Articles retrieved from a PubMed search (1989–2017) were reviewed. Demographic information, etiology, symptoms, and final vision outcomes were analyzed using Fisher's exact tests, single and multiple predictor logistic regression. Results: Of 429 articles identified, 16 were included in the study. 93 cases of retrobulbar hematoma were included. 74% occurred after trauma, while 26% occurred postoperatively. Onset of symptoms occurred after approximately 24 hours. 28% received treatment within 1 hour, 54% within 1–24 hours, and 18% after 24 hours. 51% had complete visual recovery, while 27% had partial recovery, and 22% developed blindness. Older patients and patients who sustained trauma were less likely to have a full recovery (p = 0.029, p = 0.023). Increasing number of symptoms trended towards a prediction of blindness (p = 0.092). Surgical decompression and shorter time to treatment were each highly predictive of full recovery (p = 0.024, p = 0.003) and decreased likelihood of blindness (p = 0.037, p = 0.045); use of steroids was not found to be significant. Discussion: Retrobulbar hematoma is a diagnostic and therapeutic emergency. Factors associated with improved outcomes include younger age, decreased number of total symptoms, surgical decompression, and shorter time to treatment. If recognized and treated early with surgical decompression, recovery of vision is possible.